Properties of Aerated Concrete Containing Various Amount of Palm Oil Fuel Ash, Water Content and Binder Sand Ratio - Khairunisa, Muthusamy; Nasly, Mohamed Ali; Mohd Warid, Hussin; Norhaiza, Nordin; Zahrizan, Zakaria (IEEE, 2010)
Palm oil fuel ash (POFA) which disposed as environmentally polluting waste in continuously increasing amount by Malaysian palm oil mills has lead towards the effort of studying the possibility of recycling this material. This paper presents results on the behaviour of this agro cement based aerated concrete upon usage of different ash replacement level, water content and binder sand ratio. Initially, cubes of (70.6x70.6x70.6mm) containing various replacement level of ash were produced and tested for it compressive strength. Then, the 20% replacement level of POFA which give the highest value were used for further studies. Then, the effect of water content and binder sand ratio were investigated by preparing cubes of (70.6x70.6x70.6mm) containing 20 percent ash replacement levels and tested for compression following the procedures in BS 1881 : Part 116. Integration of 20% POFA in aerated concrete lead to production of a new green product suitable for non structural application. Study also suggests appropriate water content is necessary to promote aeration process that is responsible for lightness of this material. However, integration of too much water content may promote rupture of pores and bleeding thus diminishes the strength of concrete. Sufficient cement is vital for the binding of the fine aggregates thus promoting concrete with good strength.